IMPLEMENTATION OF SEMARANG CITY REGIONAL REGULATION NUMBER 13 OF 2010 CONCERNING THE IMPLEMENTATION OF DISASTER MANAGEMENT - Agustiningsih, Dwi Ajeng Sri Sutanti; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Disaster management is an effort by the government to protect the public from the threat of disaster. The implementation of disaster management is the responsibility of the central and regional governments, then it is handed over to the regional government through the establishment of the Regional Disaster Management Agency (BPBD). Semarang City is one of the areas prone to landslides. Furthermore, this study will discuss the implementation of Semarang City regulation number 13 of 2010 on disaster management in Semarang City and the factors that influence it. The method used is descriptive qualitative method. The purpose of this study was to determine the implementation of the regulation, especially at the pre-disaster phase in situations where there is potential for disaster and the factors that influence it using the theory of George C Edwar III Model. The result showed that the implementation of the regulation was not done well because there’s still several obstacles in the its implementation. The supporting factors in this policy is communication, disposition, organizational structure and the inhibiting factors is human resources, facilities, budget. The recommendations generated from this study are needed coordination and communication with the agencies / agencies involved need to be built or improved again, additional allocation of funds so that Semarang City BPBD is able to carry out all series of activities and related human resources in the BPBD of Semarang City especially in the field of preparedness and prevention in quantity needs to be increased through the addition of staff.